Stakeholder governance and Irish sport. Issue 5 (4th May 2017) - Hassan, David; O'Boyle, Ian
Abstract: Within global sport it appears the effective management of the interdependency of national governing bodies, individual clubs and a network of stakeholder interests has never been more widely discussed. It points to a requirement for all sporting organizations to remain sensitive to what is an ever-growing dichotomy between sporting volunteers and professional salaried staff, their competing interests and objectives. It is by no means a straightforward undertaking and is particularly foregrounded in a sporting environment that attaches significance to the preservation of an amateur ideal. As many sports clubs are now faced with the challenge of offering an adequate forum through which to reflect the views of their grassroots members, whilst simultaneously facilitating greater commercial interest in their affairs, the fundamental changes facing Ireland's largest sporting body, the Gaelic Athletic Association (GAA), offers cause for timely reflection. This article argues that only through the introduction of a meaningful stakeholder model can the governance of an organization like the GAA, a social and cultural touchstone unmatched within Irish sporting life, begin to respond to these mounting and competing agendas.